(3SjQ GdaRGQis - (3CHh ESMGb,J (B188 (3g` s
(3ChdgG (B:s
(3Chdg HGH fHT bHhQge hGdQcGR s
(3BNQgG (B:s
(3hbGd QShd Gddg (B[ (3Udi Gddg Ydjg hSde (B] (3Ydjg GdSdGe (B: (3EjGi hQHG GdZdhd GdMOjK Je GdcJGH hGdMeO ddg QH GdYGdejf cKjQkG dGTQjc dg s
(3QhGjI eMeO Hf hVGM Yf CHj eQhGf GdeUjUi Yf GdeDda s
(3HChdgG Jedc HNW YHGS Hf CHUZ GdeJhai SfI (B386 (3RBNQ HNW GdeDQN Nda Hf YHO Gdedc GdeYQha HGHf HTchGd GdeJhai SfI (B578s
(3cJHJ GdfSNI Ydi Qb ZRGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B59s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs